الثقافة الشعبية وثقافة الصحراء والانفتاح على الآخر في رواية الطرحان لعبد الله كروم: Popular culture, desert culture, and openness to the other in Abdullah Karroum’s novel Al Tarhan - د.نعيمة بن الشريف (Al Manhal Research Journal, 2023)
In this research, we will try to look at the features of the Taoist popular culture and the culture of the desert, and openness to the culture of the other in the Tarhan novel, in search of the following problems: How did the creator Abdullah Karroum employ the popular culture and the desert culture in the Tarhan novel? What is his position on openness to the culture of the other?